Contemporary Administrative Codes to Identify Pulmonary Vein Isolation Procedures for Atrial Fibrillation - Enrico G. Ferro; Matthew R. Reynolds; Jiaman Xu; Yang Song; David J. Cohen; Rishi K. Wadhera; Andre d'Avila; Peter J. Zimetbaum; Robert W. Yeh; Daniel B. Kramer (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Use of pulmonary vein isolation (PVI) to treat atrial fibrillation continues to increase. Despite great interest in leveraging administrative data for real‐world analyses, contemporary procedural codes for identifying PVI have not been evaluated. Methods and Results In this observational retrospective cohort study, inpatient PVIs were identified among US Medicare fee‐for‐service beneficiaries using Current Procedural Terminology (CPT) code 93656 in Carrier Line Files. Each patient was matched with their claims from Medicare Provider Analysis and Review to compare CPT with International Classification of Diseases, Tenth Revision, Procedure Coding System (ICD‐10‐PCS) claims submitted by health care facilities to bill for PVIs. We performed the reverse for commonly matched ICD‐10‐PCS codes, to identify corresponding CPT‐billed procedures. Finally, we reviewed institutional cases for additional comparison of CPT and ICD‐10‐PCS assignation for PVI. We identified 25 617 inpatient PVIs from January 2017 to December 2021, of which 18 165 (71%) were linked to Medicare Provider Analysis and Review. Of these, 16 672 (92%) were billed as ICD‐10‐PCS 02583ZZ: “Destruction of Conduction Mechanism, Percutaneous Approach.” The reverse process yielded heterogeneous results: among 75 003 procedures billed as ICD‐10‐PCS 02583ZZ, only 15 691 (21%) matched with CPT 93656 (PVI), as several other unrelated procedures were billed under this ICD‐10‐PCS code. Institutional case review confirmed the greater specificity of CPT codes. Conclusions The ICD‐10‐PCS code associated with CPT‐billed PVI procedures actually referred to ablation of the atrioventricular junction. Yet this ICD‐10‐PCS code also matched with a wide range of other procedures distinct from PVI. We conclude that ICD‐10‐PCS codes alone are not sensitive nor specific for identifying PVI in claims and cannot be reliably used in isolation for health services research on this important procedure.